The Use Of Chatbots For Personalizing Feedback In Higher Education - Ziani, Melouka (The Journal of Studies in Language, Culture, and Society, 2025)
Artificial Intelligence (AI) has become ubiquitous, facilitating learning, including the feedback process. In fact, AI tools can be used for ‘tracking students’ progress’ (Skrabut, 2023). One of the key benefits of using AI in feedback is its ability to provide instant and personalized feedback allowing learners adjust their own learning. Besides, AI can also eliminate biases and subjectivity in feedback, ensuring a fair and objective evaluation. The present paper tries to investigate the effectiveness of AI tools for getting feedback. To achieve this purpose, an experiment was implemented to test our hypothesis. Zaplingo , an AI language model was used to see the efficiency and effectiveness of the language model in providing feedback. Some questions were addressed to the application, and then the answers and comments were identified and analyzed. The findings show that the language model provides constructive feedback, at the level of the structure, grammar, spelling, punctuation and capitalization that can enhance the writing skill. In addition, AI tools can enhance the feedback process and ultimately lead to better language learning. Yet, it is necessary not to exclude the role of the teacher in guiding the students to the best possible outcomes.